Burden of eye conditions at a specialised eye hospital in KwaZulu-Natal, South Africa - Vincent F. Verwey; Saajida Mahomed (African Vision and Eye Health, 2020)
Background: Comprehension of the burden of eye diseases in an area is essential for adequate budgeting and resource allocation.